Taḥlīl al-Akhtha’ al-Imlāiyyah fī Ta‘līm Mahārah al-Kitābah alā Ḍau’i Naẓariyati Tarigan - Ardyansyah Ardyansyah; Nurhadi Nurhadi; Danial Hilmi (IAIN Salatiga, 2020)
This study aimed at describing and analyzing the forms and the factors of writing errors at Darul Luhah wa al-Dirasat al-Islamiyah Islamic boarding school Pamekasan Madura. This research is a descriptive qualitative type. To achieve these objectives, researcher used the Glesser and Strauss model to analyze data called the fixed comparison model consisting of four steps: data reduction, data categorization, coding, and preparing working hypotheses. The results of this study showed that students errors in writing at Islamic boarding school Pamekasan Madura are mistakes in adding letters, subtracting letters, writing letters that sound alike, replacing letters or words, splitting letters or words, writing hamzah in the middle of sentences, connecting letters or words, writing hamzah qatha, writing hamzah above the line, and writing hamzah individually. The factors that influence students writing errors at Darul Lughah wa al-Dirasat al-Islamiyah are individual differences, students weakness in Arabic rules, students weakness on vocabulary mastery, students weakness on listening, the use of learning method, the absence of specific book for imla 'study, and limited time.